Genetic Management Applied to Conservation of Reduced and Fragmented Wild Populations - Moraes, Andreia Magro [UNESP]; Souza Lima, Jacqueline de; Alexandre, Brenda Rocha; Ayala-Burbano, Paola Andrea; De Freitas, Patrícia Domingues; Ruiz-Miranda, Carlos Ramon; Miyaki, Cristina Yumi (Springer Nature, 2023)
Most neotropical species are threatened by the reduction and fragmentation of their distribution range. Genetic management is an important conservation strategy for species that have small populations and little or no inter-population gene flow. Particularly, in situ genetic management of reduced and fragmented populations should be applied (i) to increase the population size and reduce loss of genetic diversity and the deleterious effects of inbreeding, and (ii) to reestablish gene flow among isolated groups. Furthermore, the importance of management measures for genetic conservation cannot be ignored given the actual context of climate change. Here, we discuss when and how translocation and reintroduction are useful strategies for the conservation of threatened species. Therefore, these actions should be done in combination with other strategies, such as habitat restoration, to guarantee a minimum population size and gene flow among the populations after human-mediated dispersal. Finally, we discuss what we learned from the genetic management of neotropical species such as lion tamarins, Spix’s macaws, and plants. Based on these programs, we highlight recommendations for planning conservation management within the neotropical forests.